Anti-Neoplastic Studies Of Standardized Root Extract Of Eurycomal Longifolia (Taf273) Towards Leukaemia - Mohammed, Omar Saeed Ali (2013)
The anti-neoplastic activity of root extracts from Eurycoma longifolia was investigated towards leukaemia using in vitro and in vivo models. Four partially purified sub-fractions (F1, TAF273, F3 and F4) derived from resin chromatography of the crude methanolic extract of E. longifolia roots were screened for the anti-leukaemic, anti-angiogenic and anti-oxidant activities. The in vitro anti-leukaemic activity was tested using K-562, HL-60 and Kasumi-1 leukaemic cell lines whereas in vivo anti-leukaemic activity was tested using K-562-xenograft mice model. The toxicity, mechanism of action and drug combination effect of TAF273 were also investigated.